Stanley, Johnson County - Page, Griffin (Kansas State University, The Chapman Center for Rural Studies, 2013)
The following paper is a history of the town of Stanley, Oxford Township, Johnson County, Kansas. Stanley was an unincorporated community that was annexed by Overland Park in 1985 despite resistance from residents. The information was mainly compiled from old newspaper articles, a book on the early history of the area, and from interviews of former Stanley locals.
Griffin Page, “Stanley, Johnson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/128.
Keywords: Stanley; Johnson County; Overland Park; John McCaughey; Blue Valley; Chief Black Bob